Prognostic value of interleukin-33, sST2, myeloperoxidase, and matrix metalloproteinase-9 in acute aortic dissection - Jia, Yu; Li, Dongze; Yu, Jing; Jiang, Wenli; Liu, Yi; Li, Fanghui; Li, Wentao; Zeng, Rui; Liao, Xiaoyang; Wan, Zhi (Frontiers in Cardiovascular Medicine, 2023)
Background and Purpose: Acute aortic dissection (AAD) is a life-threatening cardiovascular emergency. Both neutrophil granzyme and interleukin (IL)-33/ST2 systems have proven to be effective diagnostic markers for AAD. This study aimed to investigate the relationship between plasma IL-33, soluble suppression of tumorigenesis-2 (sST2), myeloperoxidase (MPO), and matrix metalloproteinase (MMP)-9 levels at admission and all-cause mortality in patients with AAD. Methods: A total of 155 patients with AAD were enrolled from the Prospective Evaluation of Acute Chest Pain (PEACP) study. Plasma concentrations of IL-33, sST2, and MMP-9 were measured using an enzyme-linked immunosorbent assay, and MPO was detected using a chemiluminescence immunoassay. Aortic anatomical parameters were measured using CT radiography. The primary endpoint was all-cause mortality rate. Results: The median age of the patients was 55 years, and 96 (61.9%) were diagnosed with type A-AAD. After adjusting for confounding factors, the highest tertiles of IL-33, sST2, MPO, and MMP-9 had hazard risks of 0.870 (95% CI: 0.412-1.836, P = 0.714), 3.769 (95% CI: 1.504-9.446, P = 0.005), 4.689 (95% CI: 1.985-11.076, P < 0.001), and 4.748 (95% CI: 1.763-12.784, P = 0.002), respectively, compared to the lowest tertile. Pearson’s correlation analysis revealed a significant correlation between these markers (P < 0.001). Moreover, sST2, MPO, and MMP-9 levels had a significant positive correlation with aortic diameter and pseudolumen area (P < 0.001). Conclusion: The biomarkers sST2, MPO, and MMP-9 were independently associated with mortality in patients with AAD. The significant correlation between these biomarkers suggests a pathogenic role for the IL-33/ST2/neutrophil granzyme system in patients with AAD.